A study of home security awareness among selected Filipino homeowners - Balberona, Audrey M. (UP College of Home Economics, 2011)
This descriptive study sought to discover the awareness on home security among selected Filipino homeowners based on their perceptions on home security and the mechanical security measures they applied in their homes. A qualitative-quantitative approach was employed in the study. Interview, observation, and photo documentation were the methods used for data collection. Twelve respondents were selected for the study through snowball sampling. The instruments included interview schedules, observation checklists, voice recorder, and a digital camera. Findings showed that the selected homeowners considered security an important aspect of their homes and gave equal value and protection to assets such as life and material possessions. Even so, eight homeowners did not see assets as a reason for possible security threats. All 12 homeowners recognized security threats only when they experienced several security-related incidents. All of them also mentioned locks and grills among measures that they use to counter threats or secure their homes, however, they relied on fences, gates and organizational security measures as well for protection. The mechanical security measures applied by the homeowners on doors and windows were generally inferior, lax and outdated. These measures were generally unsatisfactory in terms of door design, construction, material, lock, accessory, and window type, material, jamb material, and lock. Although the living areas had the highest provision for security, they were still inadequately protected based on overall assessment. In conclusion, the findings of the study showed inadequate awareness on home security among the selected homeowners based on their perceptions on home security and their actual application of mechanical security measures in their homes.